McDonaldisasi Islam: Potret Keberagamaan Muslim Kontemporer - Sutikno; Kholiq, Abd. (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
This article explores the phenomenon of the McDonaldization of Islam as a transformation of religious expression within contemporary Muslim societies, driven by technological capitalism and global cultural industries. Employing a qualitative approach and critical discourse analysis, the study reveals how digital da’wah practices are commodified and instrumentalized through mechanisms such as viral content, simulation, and performativity—mirroring the logic of the fast-food industry. This trend not only signifies a shift in the meaning and function of da’wah but also reflects the ideological hegemony of digital capitalism over religious practices. In this context, ideological critique is essential to reconstruct the prophetic foundations of Islamic preaching. The study highlights the urgency of multidisciplinary approaches in understanding the dynamics of digital religious communication and underscores the need for resistance against the distortion of spiritual values under the forces of global cultural capitalism.